Bioversity International Annual Report 2006 - Bioversity International (Bioversity International, 2007)
This is the second annual report to be published under the name of Bioversity International. It provides a detailed overview of Bioversity's activities in agricultural biodiversity research aimed at improving the lives of current and future generations.